Pathogenetic Relationship of Immunological Disorders in Chronic Generalized Periodontitis and Rheumatoid Arthritis - G. V. Poryadin; A. N. Zakhvatov; A. Y. Parshina (Архивъ внутренней медицины)
The pathogenetic mechanisms of progression of chronic periodontitis accompanied with rheumatoid arthritis is confirmed by the common parts of immune-inflammatory reactions.Damage to periodontal tissues is indirectly made by cytotoxic effects of enzymes and their metabolites produced by Porphyromonas gingivalis bacteria. Neutrophils contribute to the progression of periodontitis and participate in its amplification by recruiting T-helper cells 17 and contributing to the accumulation of plasma cells in the affected tissues. Activation of immunocompetent cells promotes the generation of reactive oxygen species that initiate free radical oxidation of lipids, which, combined with the inability to neutralize them due to reduced antioxidant potential, leads to the development of oxidative stress.The connection between rheumatoid arthritis and chronic periodontitis has been the focus of numerous studies, due to their common pathogenetic mechanisms. Chronic inflammation associated with both rheumatoid arthritis and chronic periodontitis is similar in its prevailing adaptive immune phenotype, an imbalance between pro- and anti-inflammatory cytokines. The involvement of the Porphyromonas gingivalis microorganism in the generation of antibodies to citrullinated peptides in patients with rheumatoid arthritis is significant. The similarity of the epitope (SE) encoding the HLA-DRB1 allele, binding citrullinated peptides, can act as a basis for the approval of the genetic predisposition and mutual potential of these diseases. Thus, the proven connection between chronic periodontitis and rheumatoid polyarthropathies determines the significance of the analysis of the data obtained and substantiates the need for strategic research aimed at developing new methods in the diagnosis, treatment and prevention of the diseases for the purpose of breaking and separation of the common pathogenetic mechanisms of inflammatory reactions and osteoresorption processes leading to persistent functional and organic disorders.